The decoy oligodeoxynucleotide against HIF-1α and STAT5 ameliorates atopic dermatitis-like mouse model - Mi-Gyeong Gwon; Jaechan Leem; Hyun-Jin An; Hyemin Gu; Seongjae Bae; Jong Hyun Kim; Kwan-Kyu Park (Elsevier, 2023)
Atopic dermatitis (AD) is a common inflammatory skin disease caused by an immune disorder. Mast cells are known to be activated and granulated to maintain an allergic reaction, including rhinitis, asthma, and AD. Although hypoxia-inducible factor-1 alpha (HIF-1α) and signal transducer and activator of transcription 5 (STAT5) play crucial roles in mast cell survival and granulation, their effects need to be clarified in allergic disorders. Thus, we designed decoy oligodeoxynucleotide (ODN) synthetic DNA, without open ends, containing complementary sequences for HIF-1α and STAT5 to suppress the transcriptional activities of HIF-1α and STAT5. In this study, we demonstrated the effects of HIF-1α/STAT5 ODN using AD-like in vivo and in vitro models. The HIF-1α/STAT5 decoy ODN significantly alleviated cutaneous symptoms similar to AD, including morphology changes, immune cell infiltration, skin barrier dysfunction, and inflammatory response. In the AD model, it also inhibited mast cell infiltration and degranulation in skin tissue. These results suggest that the HIF-1α/STAT5 decoy ODN ameliorates the AD-like disorder and immunoglobulin E (IgE)-induced mast cell activation by disrupting HIF-1α/STAT5 signaling pathways. Taken together, these findings suggest the possibility of HIF-1α/STAT5 as therapeutic targets and their decoy ODN as a potential therapeutic tool for AD.